(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
Our given article we have made a comparative analyzed that definitions given to the word "term" by scientists who conducted scientific research on Turkish terminology. Firstly, the unity of "term" primarily distinguished from other units, because of its scientific feature. Its communicative qualities originated from its meaning.